Synergetic contribution of fluorinated azide for high EQE and operational stability of top-illuminated, semitransparent, photomultiplication-type organic photodiodes. Issue 11 (27th September 2021) - Kim, Juhee; Joo, Chul Woong; Hassan, Syed Zahid; Yu, Seong Hoon; Kang, Mingyun; Pi, Jae-Eun; Kang, Seung-Youl; Park, Young-Sam; Chung, Dae Sung
Abstract : A fluorinated azide can improve the EQE and long-term stability of photomultiplication-type organic photodiodes (PM-OPDs). The resulting top-illuminated, semitransparent, stable, and high-EQE PM-OPD is successfully applied to a fingerprint sensor. Abstract : In this study, it is shown that fluorinated azide, employed as a functional additive to photomultiplication-type organic photodiodes (PM-OPDs), can not only enhance the operational stability by freezing the morphology consisting of matrix polymer/localized acceptor but also stabilize the trapped electron states such that the photomultiplication mechanism can be accelerated further, leading to exceptionally high external quantum efficiency (EQE). The consequent semitransparent OPD consisting of molybdenum oxide (MoO3 )/Au/MoO3 /photoactive layer/polyethyleneimine ethoxylated/indium tin oxide (ITO) rendered a maximum EQE of over 500 000% and 370 000% under bottom and top illumination, respectively. Owing to the remarkably high EQE, high specific detectivity of 5.6 × 10 13 Jones and low noise-equivalent power of 5.35 × 10 −15 W Hz −0.5 were also demonstrated. Furthermore, the OPD demonstrated stable performance during 20 h of continuous operation and minimal performance degradation even after the damp heat test. To fully visualize the advantages of the proposed high-EQE, top-illuminated, semitransparent OPD with spectral asymmetry between absorption and detection, a reflection-type fingerprint platform consisting of 1 OPD-1 oxide field-effect transistor complementary metal–oxide–semiconductor backplane (300 ppi) is designed and fabricated. The successful recognition of the fingerprint of one of the authors is demonstrated, which indicates the feasibility of the proposed PM-OPD for sensing weak light intensity.